1989
DOI: 10.1007/bf01456165
|View full text |Cite
|
Sign up to set email alerts
|

A two-year prospective follow-up study of the outcome after surgery in patients with slipped lumbar disk operated upon for the first time

Abstract: 57 patients who were operated upon for the first time for slipped lumbar disk have been investigated in a prospective blind follow-up design. In both the preoperative and postoperative evaluation objective as well as subjective conditions have been considered, and the surgeons have not re-examined the patients. There is a 100% follow-up of the patients. We found that the following preoperative conditions are associated with surgical outcome, 6 and 24 months postoperatively: Medical parameters like statement of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

1990
1990
2004
2004

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…For example, among patients who have undergone lumbar disc surgery, those with postoperative medical complaints reported lower satisfaction in family and social support than those patients with no postoperative medical complaints. 8,14 More generally, social support has been negatively associated with morbidity among patients with musculoskeletal disorders. 7 On a more positive note, social support from a spouse has been positively associated with pain relief up to 2 years after spinal decompression surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, among patients who have undergone lumbar disc surgery, those with postoperative medical complaints reported lower satisfaction in family and social support than those patients with no postoperative medical complaints. 8,14 More generally, social support has been negatively associated with morbidity among patients with musculoskeletal disorders. 7 On a more positive note, social support from a spouse has been positively associated with pain relief up to 2 years after spinal decompression surgery.…”
Section: Discussionmentioning
confidence: 99%
“…13 Furthermore, those patients who are unemployed at the time of surgery tend to have poorer postoperative outcomes. 14,15 There may also be social incentives that negatively impact patients' recovery. Researchers have found increases in reported pain, disability, and psychological distress among those with chronic low back pain who are also receiving workers' compensation benefits compared to those not receiving benefits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several predictors of an unfavourable outcome have been identified [1,2,12,20,25,28,30,31,32] and socioeconomic and psychological factors seem to play a major role [7,9,15,21,24]. Risk factors for deterioration of functional status and HRQL after microdiscectomy have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies reported on increase in pain after microdiscectomy [17,26,29] and one study reported on decrease in health-related quality of life (HRQL) after such operations [30]. Prospective studies focusing on deterioration of functional status after microdiscectomy are lacking.Several predictors of an unfavourable outcome have been identified [1,2,12,20,25,28,30,31,32] and socioeconomic and psychological factors seem to play a major role [7,9,15,21,24]. Risk factors for deterioration of functional status and HRQL after microdiscectomy have not been reported.…”
mentioning
confidence: 99%